Fungal community survey of Fraxinus excelior in New Zealand - Chen, Jie (SLU/Dept. of Forest Mycology and Plant Pathology, 2012)
The European Ash tree (Fraxinus excelsior) is widely grown throughout Europe. As a large deciduous tree species, it grows a tall, domed crown and has an attractive tree shape, so it is considered as a popular amenity tree species. European Ash is planted as an important forestry species in some European countries, and also often used for furniture making, due to its excellent wood quality. Ash species were introduced into New Zealand upon colonization in the 1800s. Recently, ash trees throughout Europe have been observed to become damaged or die due to a severe disease known as ash dieback, caused by the fungus Chalara fraxinea. We are concerned about what will happen to the introduced ash tree in New Zealand. To our knowledge, there have been no studies on the fungi that inhabit ash trees in New Zealand. It is unknown which fungal species were present in ash at the time of the introduction to New Zealand, or which New Zealand fungi colonized ash tree after the introduction. Currently, ash dieback is not believed to be present in New Zealand. The aim of this project was to determine the possible fungal communities on ash trees in New Zealand. We collected bark, bud and wood from three healthy ash trees, and used DNA-based methods to identify the fungi that inhabited these trees. We compared our study with a similar Swedish study to find differences and similarities in the fungi present on New Zealand and European ash trees. In total, we found 90 different fungal species. Of these species found, seven fungi could be species that came to New Zealand with the introduced ash tree. We also found one fungus that could possibly be said to have come from New Zealand. The pathogen causing ash dieback, Chalara fraxinea, was not detected.